Serum levels of copper, zinc and magnesium in pregnant women with Impaired Glucose Tolerance test: a case control study - Roshanravan, Neda; Mesri Alamdari, Naimeh; Ghavami, Abed; Mousavi, Reihaneh; Alipour, Shahriar; Ebrahimi-Mamaghani, Mehrangiz (Progress in Nutrition, 2018)
Objective: Gestational diabetes mellitus (GDM) is a type of diabetes that begins during pregnancy. This problem causes many complications for mother and foetus. Mineral levels in diabetic patients change and since the levels of these elements have not received much attention in patients with impaired glucose tolerance test (IGT), in this study serum concentration of copper (Cu), zinc (Zn), and magnesium (Mg) were analysed in singleton pregnant women with IGT compared with euglycemic pregnant women. Methods: The subjects of this case-control study have been selected from pregnant women who referred to Rohzendeh health and therapeutic center in northwest of Iran from December 2013 - April 2014. 46 pregnant women with IGT and 35 euglycemic women were selected. The levels of hemoglobin, hematocrit, zinc, copper and magnesium in the blood samples were measured. Results: The findings of this study indicated that the difference of hemoglobin and hematocrit and magnesium levels was not significant between two groups. The difference of copper concentration in healthy pregnant women and women with IGT was statistically significant (P